(untitled) - FAO (Rome, 1999)
The workshop reviewed the situation with regard to problems associated with shrimp exploitation as well as the multi-sectoral structure in place for consultation on such issues in each country. It was generally agreed that the present exploitation pattern for shrimp in most countries is non-sustainable, mainly because of capture of juvenile fish and overfishing. The workshop agreed on follow-up activities, which included preparation of detailed reports about the shrimp fisheries in each country, and venues for four regional workshop to be arranged in Dicember 1999/January 2000
Keywords: fisheries